Structural Equation Modeling of Teaching Behavior in Internet Use of Teachers in Thailand - Paitoon Pimdee; Punnee Leekitchwatana (My University, 2019)
At present, instruction via the internet is a challenge for teachers. Many teachers have changed their teaching behavior (TB) from a conventional style into a style of teaching via the internet. For this reason, this research had the objective to develop a structural equation model (SEM) of TB in internet use of lower secondary (LS) school teachers, classified according to school size. The developed SEM model of TB in internet use of LS school teachers had validity that was congruent to the empirical data of every model with good criteria of all goodness of fit indices. The model was composed of 8 latent variables from 24 observed variables. All causal variables in the model had a positive direct effect on TB in internet use, and these were able to explain the variation in TB in a large sized school, a very large sized school, and an extra-large sized school, with 99, 100, and 92, respectively.
Keywords: Online and Blended Learning